Characterizing photoinhibition and photosynthesis in juvenile-red versus mature-green leaves of Jatropha curcas L - Ranjan, Sanjay (Plant physiology and biochemistry : PPB, 2014)
Copyright © 2014 Elsevier Masson SAS. All rights reserved.